Application of pesticide in pest management: the case of lowland vegetable growers - Abu Baka, Halimatunsadiah; Mazlan, Norida; Omar, Dzolkhifli; Kamarulzaman, Nitty Hirawaty (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
This study investigates pest management practices among lowland farmers on growing leafy and fruit vegetables, particularly focusing on the pesticide usage in controlling pest. In Malaysia, vegetable productions in lowland areas are to some extent really important as in the highland areas due to the wide marketing channel, from local till traded across border. Yet, the ignorance of vegetables safety regarding the appropriate of pesticide usage by farmers was undeniable, as the market demands only products with good extrinsic quality. Thus a survey was conducted among of 85 of lowland vegetable farmers to get information on their pest management practices in farms. Result showed that the pesticide application by farmers on vegetables crops still indicated a calendar spraying practices. In most cases, farmers tend to harvest the vegetable products shortly after a few days of last pesticide spraying. In order to enhance the food safety control starting from the primary production, extensive monitoring of the current pesticide usage by farmers in vegetable productions is vital to provide an updated data on the food safety risk regarding to the pesticide residues. Therefore, the thrust of this paper was to get a better understanding on the level of safe pesticide usage among vegetables farmers especially in areas of growing vegetables productions.